Sustainability of Community-Based Drinking Water Service System in Sukadana Village and Ababi Village, Karangasem Regency - I Gusti Ayu Lia Yasmita (Syntax Corporation Indonesia, 2023)
Water is one of the basic needs that must be met by all human beings. In fulfilling this, the government's participation plays a very important role, limited fund management is a scourge that is feared by the government so that the coverage of community-based drinking water services with independent management from the community is the first step in overcoming the current achievement of access to drinking water. However, in its development the SPAM system built has experienced different developments. This study aims to determine the sustainability of community-based drinking water service systems by looking at the supporting factors for the sustainability of community-based drinking water services. This study uses a qualitative method which uses a case study method. The research design used a holistic multi-case study using two research villages, namely Sukadana Village and Ababi Village. From the research results it can be seen that community-based drinking water supply has different levels of sustainability. Villages that have a level of sustainability from several aspects such as social, economic, institutional aspects make it possible to have more excellent service continuity compared to villages that only have one important aspect. This is because each aspect has a relationship between one another. The sustainability of community-based drinking water services is strongly influenced by social, human and institutional capital. Community trust in managers, commitments and rules that have been agreed upon are one of the things that support the sustainability of community-based drinking water services.